Management of Avulsive Injury After Occupational Accident: 2 Steps to Provide Better Outcomes. - Brito, Gabriel Conceição; Piassi, Jonathas Eduardo Virgilio [UNESP]; de Souza Santos, Anderson Maikon; de Lima Neto, Tiburtino José; Lopes, Gabriela Kalinsqui; Faverani, Leonardo Perez (Wolters Kluwer, 2025)
Avulsive injuries of the maxillofacial complex can be challenging to manage, particularly when both soft and hard tissues are involved. These cases often present difficulties in achieving successful reconstruction. This report presents a case of avulsive injury resulting from an occupational accident. The patient sustained a comminuted symphyseal fracture along with the loss of both bone and soft tissue. Treatment was carried out in 2 stages: initial stabilization of the soft tissues, followed by bone reconstruction using iliac crest bone grafts. Both procedures were complemented by photodynamic therapy. Although such injuries are complex, avulsive fractures require meticulous assessment to determine the extent of tissue involvement and to select the most appropriate surgical techniques and adjunctive therapies. A tailored approach is essential to optimize functional and aesthetic outcomes.